AN ANOMALOUS VENA CAVAL RETURN TO LEFT ATRIUM PRESENTING AS RECURRENT ABORTIONS: A CASE REPORT - Masud, Mohsin; Shafi, Yasir; Abaidullah, Sajid (Journal of Ayub Medical College Abbottabad, 2025)
Opening of inferior vena cava into the left atrium with atrial septal defect is an extremely rare congenital abnormality. We report a case of 28-years-old female presented with repeated respiratory tract infections and repeated abortions 19 years after the repair of atrial septal defect and partial anomalous pulmonary venous return. Investigations showed that she was also having abnormal drainage of inferior vena cava into the left atrium. This drainage was causing hypoxemia leading to repeated abortions. Second surgery was performed which confirmed the drainage of inferior vena cava into the left atrium. The repair was carried out with subsequent correction of hypoxemia and successful pregnancy.